Calculation of Zn, Cd, Hg adsorption on graphene with incremental CCSD(T) and range-separated hybrid DFT*. (17th April 2016) - Weber, Fabian; Müller, Carsten; Paulus, Beate; Reinhardt, Peter
ABSTRACT: At the hand of the adsorption of the metal atoms Zn, Cd and Hg on a graphene sheet, we propose a combination of range-separated hybrid density-functional theory in combination with the incremental scheme in localised orbitals and extrapolation procedures for the description of this type of extended systems. Using only dispersion terms for the long-range part, we were able to obtain results comparable to incremental coupled-cluster calculations with singles, doubles and perturbative triples (CCSD(T)). Repulsive three-centre increments reduce the overall correlation contribution to the binding energy by 20 %. GRAPHICAL ABSTRACT: